Vaccination of schoolgirls against rubella. Assessment of serological status and a comparative trial of Wistar RA 27/3 and Cendehill strain live attenuated rubella vaccines in 13-year-old schoolgirls in Dudley. Issue 4 (December 1975) - Freestone, D S; Reynolds, G M; McKinnon, J A; Prydie, J
Abstract : A total of 1525 schoolgirls aged 13 years from 21 schools in the County Borough of Dudley, were bled for titration of rubella haemagglutinating inhibiting antibody and then were immediately vaccinated with either Wistar RA 27/3 or Cendehill strain live attenuated. Both vaccines were administered subcutaneously by syringe and needle but the Wistar RA 27/3 vaccine was also given by multiple injection apparatus. Significnatly higher conversion rates and geometric mean haemagglutinating inhibiting antibody titres were obtained in girls initially seronegative given the Wister RA 27/3 than in those given the Cendehill vaccine, regardless of the method of vaccination. The RA 27/3 strain was associated with a small but significantly greater incidence of local pain immediately on injection. With this exception, differences in the occurrence of reactions were not found between vaccines, between those initially susceptible and immune or with the level of antibody response.